Association of Pre-Transplant Lymphopenia with Post-Liver Transplantation Complications - Puri, Monica; SM, Shastry; Pamecha, Viniyendra; Rana, Gursimran Singh; Bihari, Chhagan (Annals of Pathology and Laboratory Medicine, 2025)
Background: Liver transplant is a definitive cure for end-stage liver disease, but organ shortages demand better patient prioritization methods. Absolute lymphocyte count [ALC] may indicate the outcomes, though its role in early post-transplant results needs further study. Methods: This retrospective study analyzed medical records of 7-month to 75-year-old patients undergoing primary liver transplants at ILBS, New Delhi, from September 2010 to April 2023, excluding cases lacking ALC results or meeting other criteria. Results: This study included 581 patients, median age 45 years, predominantly male [476], with ethanol-induced chronic liver disease common. MELD 22.7, ascites [378]. encephalopathy [211], and CMV positivity [124]. The low ALC group had higher MELD scores, while ascites [73.7%), encephalopathy [38.7%], and CMV positivity [26.8%] were more common in the adequate ALC group. Within 30 days post-LT. bacterial infections were more common in the adequate ALC group [45% vs. 13%]. while rejection was more frequent in the low ALC group [19.6% vs. 7%]. Sepsis from gram-negative bacteria was a major cause of death. Persistent post-transplant lymphopenia [ALC<500/μL at LT and POD30] was associated with 40 of 62 patients experiencing mortality. Culture-positive infections (84.3% vs. 16.6%) and CMV (34.5% vs. 16.6%) were higher in the complication group. Conclusion: No effect of low ALC on mortality.